Impact Of Land Use/Cover Change On Soil Carbon Stocks, Livelihoods And Opportunities For Mitigation In Mt. Elgon Region - Balaba, Tumwebaze S. (Third RUFORUM Biennial Meeting, 2010)
The study was conducted to assess community perception on landuse/cover change and its impact on the their livelihood. Knowledge on community copping strategies in improving and maintaining soil carbon levels was also investigated. Analysing of the spatial and temporal pattern of land use/cover change at different altitudes in Mt. Elgon region between 1960 and 2009, a quantification of soil organic carbon (SOC) pools and fluxes with respect to the present land use were also done. The study aimed at predicting future effects of alternative land use change scenarios on soil organic carbon. It explored above-ground biomass and carbon stocks of different land cover types, i.e., tropical natural forest, cultivated lands and encroached forest to examine the total amount of carbon sequestered. Household interviews were used to obtain information on community perception on land use/cover change and its impact on the their livelihood and community copping strategies in improving and maintaining soil carbon levels. Preliminary results indicated that there were significant differences in SOC among the different land cover types, where the tropical natural forest stored more carbon compared to cultivated land and encroached forest. Soil organic carbon also significantly changed with soil depth. There was more aboveground carbon sequestered in the forest compared to encroached and cultivated land. Encroachment on tropical natural forest resulted into a loss of 84.3% of the above ground carbon sequestered. This study recommends that existing natural forests be conserved to avoid loss of carbon which contributes to carbon dioxide, a greenhouse gas involved in global warming.
Keywords: Carbon sequestration, carbon stocks, land use, land cover change, Mt. Elgon, soil carbon, Uganda